The evolution and trend of chain code scheme - Wulandhari, Lily Ayu; Haron, Habibollah (Academic Manuscript Central, AMC, 2008)

(untitled)
Chain code is an image method representation based on region boundaries. The chain code of region is determined by specifying a starting pixel and the sequence of unit vectors obtained from going either left, right, up, or down in moving from pixel to pixel along the boundary. Chain code is widely used nowadays because it preserves information and allows considerable data reduction. The first approach for representing digital curves using chain code was introduced by Freeman in 1961, and it is known as Freeman Chain Code (FCC). This code follows the contour in counter clockwise manner and keeps track of the directions as we go from one contour pixel to the next. The codes involve 4– connected and 8– connected paths. Since it was introduced by Freeman, the development of chain code and its application increases rapidly. This paper explains some chain code concepts and their applications that are be the background of the development of vertex chain code cells algorithm. This algorithm is able to visualize and to transcribe a binary image into vertex chain code easily. Some examples are also presented.